Reindeer hunters at Howburn Farm, South Lanarkshire : a late Hamburgian settlement in Southern Scotland - its lithic artefacts and natural environment - Ballin, Torben Bjarke, (Archaeopress Publishing Ltd, 2018)
This volume presents the lithic assemblage from Howburn in South Lanarkshire, Scotland, which at present is the oldest prehistoric settlement in Scotland (12,700-12,000 BC), and the only Hamburgian settlement in Britain. The site also included a scatter from the Late Upper Palaeolithic Federmesser-Gruppen period (12,000-10,800 BC), as well as lithics from the Mesolithic, Neolithic and Early Bronze Age. The text focuses on the Hamburgian finds, which are mainly based on the exploitation of flint from Doggerland, the then dry bed of the North Sea.